A phase II Bayesian sequential clinical trial in advanced Waldenström macroglobulinemia patients treated with bortezomib: interest of addition of dexamethasone. Issue 11 (2nd November 2017) - Leblond, Véronique; Morel, Pierre; Dilhuidy, Marie-Sarah; Leleu, Xavier; Soussain, Carole; Leprête, Stéphane; Dreyfus, Brigitte; Dartigeas, Caroline; Mahé, Béatrice; Anglaret, Bruno; Pégourié, Brigitte; Besson, Caroline; et al.
Abstract: In patients with advanced Waldenström macroglobulinemia (WM), overall response rate (ORR) and median progression-free survival (PFS) achieved with bortezomib alone and bortezomib rituximab combination were 27–85% and 7.9 months, and 81% and 16.4 months, respectively. We checked the role of dexamethasone in combination with bortezomib by enrolling in a phase II trial 34 patients with relapsed/refractory WM. Bortezomib (1.3 mg/m 2 IV D1, 4, 8, and 11 every 21 days) was used for six cycles. In non-responding patients, dexamethasone (20 mg daily for two days) was added to each infusion after the second cycle. After two cycles, the Bayes estimated ORR was 43.2 (95% Credible Interval: 28.0–59.1%) using the informative prior. Two-year survival rate was 84.0% and the median PFS 15.3 months without difference between patients treated with or without dexamethasone. We conclude that dexamethasone must be associated to bortezomib-based regimen.